ARTEMIS Observations of Lunar Nightside Surface Potentials in the Magnetotail Lobes: Evidence for Micrometeoroid Impact Charging. Issue 15 (6th August 2021) - Poppe, A. R.; Xu, S.; Liuzzo, L.; Halekas, J. S.; Harada, Y.
Abstract: The Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun mission observes anomalously low lunar nightside surface potentials while in the terrestrial magnetotail lobes. Observed potential magnitudes are between 15% and 40% that expected from ambient tail‐plasma charging, are highly concentrated on the lunar dawn hemisphere, and are correlated with low ambient plasma densities. These characteristics suggest an additional, highly asymmetric source of cold current to the lunar surface. Given these characteristics, we identify micrometeoroid impact‐generated plasmas as the likely source of this additional current. Using laboratory measurements of impact charge yields and models of the micrometeoroid flux to the Moon constrained by in situ measurements, we show that currents due to micrometeoroid impact plasmas have the necessary magnitude and spatial distribution to explain the observed surface potential measurements. Micrometeoroid impact‐generated currents may contribute to surface charging at airless bodies with intense micrometeoroid bombardment and/or low ambient plasma densities. Plain Language Summary: Since the Moon lacks a thick atmosphere, both external plasmas and interplanetary micrometeoroids directly interact with the lunar surface. Consequently, the lunar surface builds up a static electric potential that balances all electric currents. NASA's Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) mission can remotely determine the electrostatic potential of the lunar surface by observing electrons as they pass by the spacecraft, interact with the lunar surface, and return to the spacecraft with modifications to their flux and energies. We report ARTEMIS observations of lunar surface electrostatic potentials that are not well‐described by the theory that only considers contributions from ambient plasma. These observations show that electrostatic potentials on the lunar nightside and dawnside are lower in magnitude than expected, especially when the ambient plasma density is very low. We show that these ARTEMIS observations can be explained by invoking the production of plasma due to interplanetary micrometeoroids impacting the lunar surface. This impact plasma alters the electrostatic charge equilibrium on the lunar surface, leading to lower‐than‐expected surface potentials. By implication, micrometeoroid impact plasmas may play an important role in the surface charging of airless bodies throughout the solar system, especially when the micrometeoroid flux is particularly high or the ambient plasma flux is particularly low. Key Points: Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun observes negative surface potentials on the lunar nightside in the magnetotail lobes smaller than expected from tail‐plasma charging Observed events are concentrated primarily on the lunar dawn hemisphere and are correlated with low ambient plasma densities Micrometeoroid impact plasmas are a dominant source of current on the lunar nightside under low‐density ambient plasma conditions